Mechanisms of glutamate release from astrocytes - Parpura, Vladimir (Henry Stewart Talks, 2011)
Reversal of glutamate uptake, Anion channel opening induced by cell swelling, Ca2+-dependent exocytosis, Glutamate exchange via the cystine-glutamate antiporter, Release through ionotropic purinergic receptors, Functional unpaired connexons, 'hemichannels'
Reviewed at 2020/05/01